Developing Green Leadership in Schools: A Principal's Journey Through Biographical Narrative Analysis for Environmental Sustainability - Prasetyo Agung Darmawan; Sururi Sururi; Suryadi Suryadi; Asep Dikdik (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2025)
This study identifies the successful green leadership practices of a primary school principal, serving as a reference for other educational leaders in responding to the global environmental crisis. The Biographical Narrative Interpretive Method (BNIM) was employed to explore the principal's leadership journey through narrative inquiry, with data collected through interviews, observations, and document analysis. Findings were analysed using BNIM procedures, presented thematically, and visualised using NVivo software. The study reveals patterns of green school leadership that contribute to the development of leadership Theory through three specific technical contributions. Methodologically, this research introduces BNIM as a novel approach to exploring environmental leadership development in educational sectors. Theoretically, it establishes an operational framework for green school leadership, comprising five personal values and six measurable leadership practices. It provides a proven implementation model for effectively addressing school environmental challenges. Research contributions are demonstrated through concrete solutions to school environmental problems, including the elimination of waste bins through the universal adoption of reusable containers by students and the transformation of the school into a pilot site for cultivating 60 horticultural trees, promoting sustainable ecological learning. Additionally, six measurable leadership strategies were implemented, encompassing the establishment of vision, sharing environmental knowledge, inspirational communication, stakeholder engagement, proactive behavior, and long-term commitment. These strategies effectively address waste management challenges, promote environmental awareness within the school community, and significantly contribute to the development of green leadership practices in educational institutions